2022
DOI: 10.1371/journal.pone.0261102
|View full text |Cite
|
Sign up to set email alerts
|

Host induced gene silencing of the Sclerotinia sclerotiorum ABHYDROLASE-3 gene reduces disease severity in Brassica napus

Abstract: Sclerotinia sclerotiorum is a pathogenic fungus that infects hundreds of crop species, causing extensive yield loss every year. Chemical fungicides are used to control this phytopathogen, but with concerns about increasing resistance and impacts on non-target species, there is a need to develop alternative control measures. In the present study, we engineered Brassica napus to constitutively express a hairpin (hp)RNA molecule to silence ABHYRDOLASE-3 in S. sclerotiorum. We demonstrate the potential for Host In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…AT1703 plants demonstrate significant ABHYDROLASE-3 transcript reductions in S. sclerotiorum at 1 and 2 dpi, while reduced lesion size and fungal load are only identified at 3 dpi relative to wild-type Col-0 plants. Wytinck et al 16 showed similar results in transgenic B. napus, with significant reductions in ABHYDROLASE-3 transcript abundance and fungal load observed at 1 and 2 dpi respectively. In contrast, prior HIGS studies targeting S. sclerotiorum www.nature.com/scientificreports/ essential genes (TRX1, OA) detected both target transcript reduction and reduced lesion size at 2 dpi in host plants 33,41 , suggesting this delay to be specific to HIGS plants targeting ABHYDROLASE-3.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…AT1703 plants demonstrate significant ABHYDROLASE-3 transcript reductions in S. sclerotiorum at 1 and 2 dpi, while reduced lesion size and fungal load are only identified at 3 dpi relative to wild-type Col-0 plants. Wytinck et al 16 showed similar results in transgenic B. napus, with significant reductions in ABHYDROLASE-3 transcript abundance and fungal load observed at 1 and 2 dpi respectively. In contrast, prior HIGS studies targeting S. sclerotiorum www.nature.com/scientificreports/ essential genes (TRX1, OA) detected both target transcript reduction and reduced lesion size at 2 dpi in host plants 33,41 , suggesting this delay to be specific to HIGS plants targeting ABHYDROLASE-3.…”
Section: Discussionmentioning
confidence: 60%
“…Limiting systemic infection has significant implications on reducing yield losses from S. sclerotiorum infection. This was demonstrated by Wytinck et al 16 , where transgenic B. napus lines expressing the same ABHYDROLASE-3 hpRNA construct against S. sclerotiorum show reduced vascular tissue colonization coupled with an increase in seed mass compared to untransformed B. napus post whole-plant S. sclerotiorum infection. As infection typically initiates on mature leaves before progressing into stem tissue through the vascular system 39,40 , it is critical to reduce vascular colonization directly at the site of infection, which can ultimately slow S. sclerotiorum progression throughout the host.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations